Understanding Metrics for Communicating the Economic Importance of Florida’s Fisheries Part I: An Overview - Edward V. Camp; Christa D. Court; Andrew Ropicki; Robert Botta (EDIS, 2023)
Understanding the economic importance of fisheries and coastal resources is vitally important for making good management decisions that affect human communities, local businesses, and environment and ecological sustainability. However, economic “importance” is not a very specific term, and can mean completely different things to different people. We reviewed different fields of natural resource economics to and describe the different economic terms most often used. This information can help management agencies and cooperative Extension agents use the correct terminology and teach the correct terminology in their outreach.